The role of social learning in participatory planning & management of water resources - Muro, Melanie (Cranfield University, 2008)
Natural Resource Management processes are undergoing major transformations: technical and regulatory mechanisms are no longer considered sufficiently adaptive to address the complexity and uncertainty which characterise contemporary challenges in the sector, thus motivating wider use of integrated and collaborative approaches. Against this background, new models of participative management are encouraged which emphasise social learning among stakeholders. Yet, reported research which unambiguously demonstrates the role and impact of social learning remains sparse. This thesis contributes to a better understanding of the conditions under which social learning occurs, and most importantly the dynamics and benefits of social learning by systematically collecting evidence of the processes and impacts attributed to social learning. The research which employs a sequential mixed methods research design is undertaken with stakeholders involved in various engagement activities forming part of the implementation of the WFD in the UK, Ireland, and Germany and expands the still limited empirical knowledge base on social leaning in stakeholder interaction. Findings demonstrate that participatory platforms are shaped by processes of social learning although they are more noticeable as collaborative initiatives mature. Also, there is some degree of variation in the extent to which people learn or change, with stakeholders readily acquiring knowledge and improving relationships. However, the transformation of views and the development of a shared group identity seem to be limited. Findings clearly illustrate the multitude of factors that constrain the occurrence of learning processes and eventually limit the extent to which these can contribute to sustainable NRM. Foremost, this study reinforces the importance of the actual communicative learning process, the quality and intensity of which is largely influenced by the organisational arrangements and, more fundamentally, the ability of the stakeholders to shape the process.
Keywords: Participation; WFD; Social learning